Ecological Consequences from Forest Burning in the Northern Hemisphere in 2020: Results of Modeling and Quantitative Calculations - Chernogor, L. F.; Nekos, A. N.; Titenko , G. V.; Chornohor , L. L. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2021)
Purpose is quantitative estimation of the mass of emissions of combustion products, chemical elements, the energy and power of acoustic and thermal radiation caused by the forests large tracts burning in the Northern Hemisphere.Methods. Analytical review of investigation problem, theoretical and computational, numerical modeling, system analysis.Results. It was found that large-scale fires in the Northern Hemisphere in 2020 had catastrophic ecological consequences. The greatest contribution was made by the burning of forests in Russia and the USA. Ecosystems were affected on an area of about 15 million hectares. About 3,5 Gt of wood was irretrievably lost. About 140 Mt of smoke and more than 10 Mt of soot were emitted into the atmosphere. The mass of the injected CO gas was about 350 Mt. The mass of hydrocarbons emitted into the atmosphere was about 140 Mt. About 7,8 Gt of CO2 gas was additionally emitted into the atmosphere. Hundreds of megatons of atomic nitrogen, hundreds of tons of potassium and calcium, as well as from units to tens of tons of such chemical elements as Fe, Zn, Cr, Br, Mn, Pb, Rb, Sr and Se have been emitted into the atmosphere. The energy of acoustic radiation was about 100 PJ, which is almost a thousand times higher than its energy under normal conditions. The energy of weakly damped infrasonic radiation was 1–10 PJ. The thermal radiation flux density reached 56–160 kW/m2. Even after the distribution of forest combustion products around the globe, their concentration exceeded the concentration under normal conditions. This primarily applies to smoke, soot and carbon monoxide. The economic damage amounted to about 750 billion US Dollars. Dozens of people died and were injured. Material and moral damage has been caused to many thousands of people. Material and moral damage caused to many thousands of people.   Conclusions. The ecological consequences of the forests large tracts burning of Northern Hemisphere in 2020 for the planet became a kind of record.